PENGARUH TINGKAT KETINGGIAN AIR MEDIA PEMELIHARAAN TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN BENIH IKAN GABUS (Channa striata) - Muhammad Nursihan; Ayu Adhita Damayanti; Dewi Putri Lestari (Universitas Mataram, 2020)
This research aimed to know the effect of varying water level on survival rate and the growth of snakehead fish (Channa striata) seed. This study used a Completely Randomized Design with five treatments, namely P1 (water level 3 cm), P2 (water level 5 cm), P3 (water level 7 cm), P4 (water level 9 cm), P5 (water level 11 cm) and each treatment has 3 replications so that the total experiment is 15 units. The results showed that there was a significant influence (p < 0.05) on survival rate, absolute growth and specific growth, so that further tests were carried out to find out the best treatment on survival rate, absolute growth and specific growth of snake head seed, it was known that P1 (3 cm water level) is the best survival rate treatment of 91.7% for snakehead seeds. Whereas P2 (height 5 cm) is the best treatment in producing absolute and specific growth.